Study on Status of Women In India Sponsored By the Department of Social Welfare, Government of India: The Impact of Reference Group Influence on Young Adults' Purchase Decisions (Journal of Advances and Scholarly Researches in Allied Education, 2012)
There are some people that anindividual keeps in mind when making a purchase. Usually, such peopledisseminate opinions and other individuals are pressured into following theirtrend, becoming associated with them and using them as a standard of theirpurchase decisions. Such people are known as reference groups and they includeentertainment figures, sports heroes, political leaders, parents, co-workers,teachers and peers. This paper seeks to contribute to the existing body of theliterature on reference group influence. Specifically, it focuses on peerinfluence among young adults’ products purchase decisions.   A convenience sample of 101 universitystudents participated in this study. The results of Analysis of Variance andt-tests indicated that there is more normative influence for a public luxury(sunglasses) than for a private luxury (cell phone) and private necessity(toothpaste). Informational influence was also more for a public luxury than aprivate necessity.